Acute Toxicity, Immunotoxicity and Allergenicity of Protease Complex Obtained from Micromycete Sarocladium strictum - Svetlana Alipkina; Elena Kornienko; Denis Nalobin; Alexander Osmolovskiy (MDPI AG, 2021)
The different effects on animals of the thrombolytic protease complex of the new producer S. strictum 203 were studied. The tests of acute toxicity, immunotoxicity and allergenicity should conclude that the studied proteolytic complex is safe for medical usage. For the intravenous and the intraperitoneal routes of administration, the maximum tolerated dose and the median lethal dose were not determined.